2010
DOI: 10.1055/s-0030-1255442
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Activated Factor VII: Mechanisms of Action and Current Indications

Abstract: Recombinant activated factor VII (rFVIIa) was initially developed to overcome the limitations of existing treatments for patients with congenital hemophilia and inhibitors. Clinical success in this arena led to experimental use in other coagulopathies characterized by impaired thrombin generation, and approval for use in acquired hemophilia, factor VII deficiency, and Glanzmann's thrombasthenia soon followed. Extensive research and growing experience in the clinical setting has increased our knowledge of rFVII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 46 publications
(74 reference statements)
0
26
0
Order By: Relevance
“…Pertaining to the hemostatic therapy, bypassing agents (recombinant activated factor VII [rFVIIa] and activated prothrombin complex concentrates [APCC] are considered the first-line treatment option of bleeding episodes in AHA patients [36][37][38][39][40][41]. Both types of bypassing agents have been demonstrated to be effective, although there are no comparative trials to demonstrate superior efficacy for either product [42][43][44][45][46]. The efficacy of the plasma-derived product APCC (FEIBA, Baxalta, Bannockburn, IL, USA) in AHA has been documented by various reports in the literature and by a retrospective review of 34 patients, which showed an overall efficacy of 86% when the treatment was used as the first-line option at a typical dose of 75 U/kg every 8-12 hours [43].…”
Section: Hemostatic Therapymentioning
confidence: 99%
“…Pertaining to the hemostatic therapy, bypassing agents (recombinant activated factor VII [rFVIIa] and activated prothrombin complex concentrates [APCC] are considered the first-line treatment option of bleeding episodes in AHA patients [36][37][38][39][40][41]. Both types of bypassing agents have been demonstrated to be effective, although there are no comparative trials to demonstrate superior efficacy for either product [42][43][44][45][46]. The efficacy of the plasma-derived product APCC (FEIBA, Baxalta, Bannockburn, IL, USA) in AHA has been documented by various reports in the literature and by a retrospective review of 34 patients, which showed an overall efficacy of 86% when the treatment was used as the first-line option at a typical dose of 75 U/kg every 8-12 hours [43].…”
Section: Hemostatic Therapymentioning
confidence: 99%
“…Recombinant FVIIa functions in part by initiating the formation of a complex between tissue factor and factor VIIa. This increases thrombin formation and activates a downstream cascade resulting in accelerated fibrin clot formation at sites of vascular injury (Croom & McCormack, ; Franchini & Lippi, ). Hay et al () reported that treatment of 74 AHA bleeding episodes with rFVIIa was associated with a 100% response rate when the drug was used as first‐line therapy, 75% good or partial response when used as second‐line therapy, and a 17% good or partial response when used as salvage therapy (17%).…”
Section: Acute Treatmentmentioning
confidence: 99%
“…Control of bleeding can be achieved using various agents depending on the severity6 of the bleed and the concentration of the factor inhibitor (expressed in Bethesda units). DDAVP and high dose human factor VIII concentrate may be helpful with low inhibitor titres (<10 Bethesda units) and recombinant human factor VIIa7 or activated prothrombin complexes are used when there are higher inhibitor titres. Several drugs can be used to eliminate the inhibitor including high dose steroids for a minimum of 3 weeks or immunosuppressive therapies like cyclophosphamide, rituximab.…”
Section: Discussionmentioning
confidence: 99%